The Clinical Impact of Tumor Grade Heterogeneity in Nonmuscle- invasive Urothelial Carcinoma of the Bladder - Meftun Culpan; Ferhat Keser; Ayberk İplikci; Gözde Kır; Gökhan Atış; Asif Yıldırım (Medeniyet Medical Journal)
Objective: This study aimed to determine the oncological outcomes of mixed-grade tumors by comparing them with pure low-grade and high-grade tumors. Methods: We retrospectively reviewed the medical records of patients with primary non-muscle-invasive bladder cancer. Patients were categorized into three groups according to the histological grade of their tumors: low-grade, mixed-grade, and high-grade. Clinicopathological characteristics and oncological outcomes, such as recurrence-free survival (RFS), progression-free survival (PFS), and cancer-specific survival (CSS), were compared between the three groups. Results: A total of 369 patients (190 low, 40 mixed, and 139 high-grade) were included in our study, with a mean follow-up of 55.94±41.73 months. Patients with mixed-grade tumors had lower rates of pT1 stage diseases than those with high-grade tumors (42.5% vs. 64.0%, respectively) and higher rates than those with low-grade tumors (14.7% vs. 42.5%, respectively) (p=0.001). There was no significant difference in RFS between low-, mixed-, and high-grade tumor patients (p=0.887). Patients with mixed-grade tumors had worse PFS and CSS outcomes than those with low-grade tumors (199.84±23.22 vs. 214.94±15.92 for PFS and 202.07±19.86 vs. 233.61±9.84 for CSS, respectively) and better PFS and CSS outcomes than those with highgrade tumors (199.84±23.22 vs. 163.28±16.18 for PFS and 202.07±19.86 vs. 180.81±15.89 for CSS, respectively), although these comparisons were not statistically significant. Conclusions: Patients with mixed-grade tumors had worse PFS and CSS outcomes than patients with low-grade tumors and better PFS and CSS outcomes than patients with high-grade tumors, although these comparisons were not statistically significant. Our results should be verified by future studies.